2018
DOI: 10.1262/jrd.2018-029
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress impairs gap junction communication and cumulus function of bovine oocytes

Abstract: The intimate association of cumulus cells with one another and with the oocyte is important for regulating oocyte meiotic arrest and resumption. The objective of this study was to determine the effects of heat stress on cumulus cell communication and functions that may be related to accelerated oocyte meiosis during early maturation. Bovine cumulus-oocyte complexes underwent in vitro maturation for up to 6 h at thermoneutral control (38.5°C) or elevated (40.0, 41.0 or 42.0°C) temperatures. Gap junction communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
1
14
0
1
Order By: Relevance
“…Oocyte transcriptome analysis indicated a strong difference between heat‐tolerant and heat‐sensitive cow breeds, involving genes that are differentially expressed between breed, temperature and the breed × temperature interaction (Ticianelli et al, ). This is further supported by recent studies in bovine oocytes exposed to HS (41–42°C) during the first 6 hr of IVM that demonstrated alterations in gap junction communications between oocytes and cumulus cells, which, in turn, affected correct cytoplasmic maturation and accelerated the progression of oocyte meiosis (Campen et al, ).…”
Section: The Female Reproductive Tractsupporting
confidence: 60%
“…Oocyte transcriptome analysis indicated a strong difference between heat‐tolerant and heat‐sensitive cow breeds, involving genes that are differentially expressed between breed, temperature and the breed × temperature interaction (Ticianelli et al, ). This is further supported by recent studies in bovine oocytes exposed to HS (41–42°C) during the first 6 hr of IVM that demonstrated alterations in gap junction communications between oocytes and cumulus cells, which, in turn, affected correct cytoplasmic maturation and accelerated the progression of oocyte meiosis (Campen et al, ).…”
Section: The Female Reproductive Tractsupporting
confidence: 60%
“…Direct exposure of cumulus-oocyte complexes to a physiologically-relevant elevated temperature during the first half of in vitro maturation reduces embryo development [912] in a manner consistent with what has been observed after heat-induced hyperthermia occurring in vivo near the time of estrus [8, 13, 14]. Heat stress exposure during the first half of in vitro maturation heightens progesterone production and alters the transcriptome and interconnectedness of the cumulus [1517] surrounding the maturing oocyte. Heat-induced differences in cumulus function persist despite efforts to mature cumulus-oocyte complexes under thermoneutral conditions for the remainder of maturation [16].…”
Section: Introductionmentioning
confidence: 78%
“…They also provide extracellular thermoprotectants or produce regulatory molecules that activate thermoprotective mechanisms within the oocyte ( Edwards and Hansen, 1996 ). In addition, it was demonstrated that the effectiveness of gap junction-communication between cumulus cells and oocytes was reduced after heat stress ( Campen et al., 2018 ). The disturbance of oocyte and embryo development could be due to the lack of HSP70 protection for cumulus cells at 37 °C, a stress temperature only for oocytes.…”
Section: Discussionmentioning
confidence: 99%